MODELING OF PROBLEMATIC SITUATIONS IN INTERSUBJECTIVE CONTROL THEORY - T. V. Moiseeva; N. Yu. Polyaeva (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The classical management approach associated with the organisation of management processes in enterprises, regions and states is aimed at improving the efficiency of the operation of the management object, but not at solving problem situations encountered by representatives of the society. By developing a theory of joint search for solutions to problem situations in which social actors find themselves, it is proposed to supplement traditional management techniques with an intersubjective social management approach aimed at improving the quality of life of people. The aim of the research is the further development of intersubjective management theory and its supplementation by formalised means for practical application.Methods. The system approach, methods of analysis and synthesis and mathematical modeling are applied. In order to visualise the stage sequence of finding a way out of a problem situation, a method relying on graphic images is used.Results. The theory of intersubjective management for finding a way out of problematic social situations is developed. Additionally, an algorithm for analysing the problem situation and finding a solution is presented, the “problem situation” is considered in terms of the meaning of the problem situation chain, a formal mathematical model of the problem situation is constructed and the application of the basic provisions of the theory of intersubjective control is described on an example.Conclusion. The proposed scheme for analysing problematic situations complements existing theoretic using an approach that will allow it to be applied in practice.